Relating ettringite formation and rheological changes during the initial cement hydration: A comparative study applying XRD analysis, rheological measurements and modeling - Jakob, Cordula; Jansen, Daniel; Ukrainczyk, Neven; Koenders, Eddie; Pott, Ursula; Stephan, Dietmar; Neubauer, Jürgen (Materials, 2019)
In order to gain a deeper understanding of the rheological development of hydrating ordinary Portland cement (OPC) pastes at initial state, and to better understand their underlying processes, quantitative X-ray diffraction (XRD) analysis and rheological measurements were conducted and their results combined. The time-dependent relation between phase development and flow behavior of cement paste was investigated at two different temperatures (20 and 30 °C), over a period of two hours. Regarding the phase development during hydration, ettringite precipitation was identified as the dominant reaction in the first two hours. For both temperatures, the increasing ettringite content turned out to correlate very well with the loss of workability of the reacting cement paste. An exponential relationship between ettringite growth and flow behavior was observed that could be explained by applying the Krieger-Dougherty equation, which describes the influence of solid fraction on the viscosity of a suspension.
CRIS-Team Scopus Importer:2019-10-01
Keywords: Ettringite formation; Hydration kinetics; Modeling; OPC; Rheology; Scanning electron microscopy (SEM); Temperature